2018
DOI: 10.1177/1750481318771430
|View full text |Cite
|
Sign up to set email alerts
|

Exploring disempowerment in women’s accounts of endometriosis experiences

Abstract: This work explores disempowerment caused by discourses surrounding the life altering gynaecological disease of endometriosis. Despite affecting 1 in 10 women, the worldwide average diagnosis time is 7.5 years and it is mainly diagnosed when exploring infertility rather than complaints about incapacitating pain and other associated manifestations. The aim of this paper is to identify dis/empowerment caused by discourses in the health-care and social environment of women as manifested in their accounts of endome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 24 publications
1
19
0
5
Order By: Relevance
“…as urinary tract infections (UTIs), sexually transmitted diseases (STDs), etc.) found by previous studies (Bullo, 2018;Seear, 2009), where endometriosis becomes a suspect illness by a process of elimination before women are granted access to diagnostic treatments, therefore prolonging delays.…”
Section: The Challenges Of Communicating Endometriosis Painmentioning
confidence: 89%
See 1 more Smart Citation
“…as urinary tract infections (UTIs), sexually transmitted diseases (STDs), etc.) found by previous studies (Bullo, 2018;Seear, 2009), where endometriosis becomes a suspect illness by a process of elimination before women are granted access to diagnostic treatments, therefore prolonging delays.…”
Section: The Challenges Of Communicating Endometriosis Painmentioning
confidence: 89%
“…This was also acknowledged in Kaler's (2005) data where the author reported on women being happy with a diagnosis, no matter how serious or critical it was. Along these lines, Bullo (2018) found that women who eventually achieved a diagnosis for endometriosis, after years or even decades of struggle with disbelief over the severity of their symptoms, saw the act of achieving a diagnosis as metaphorically winning a war. Similarly, Greenhalgh (2001), in her journey through a misdiagnosis of fibromyalgia that had severe consequences for her physical and mental health, addresses the methods by which diseases come to be constructed by doctors, the discourses of objectification of the ailed body, the dismissal of symptoms that cannot be quantified, and the dynamics of the doctor-patient relationship.…”
Section: The Challenges Of Communicating Endometriosis Painmentioning
confidence: 99%
“…In fact, studies of accounts of endometriosis experiences using interview data (e.g. Bullo, 2018) have found that the fighter identity is mostly associated with the difficulties in achieving a diagnosis and the perceived 'battle'…”
Section: Resultsmentioning
confidence: 99%
“…This normalisation also occurs because experiences and beliefs about endometriosis-related pain and gynaecological pain more generally are gendered, bound up in what women are expected to feel and put up with. 3,26,27 Women are expected to deal with severe pain within the confines of daily life without complaint, creating discourses of disempowerment 39 and consequences for those who cannot or will not accept this burden. 26 Research has also found that women with endometriosis often lack the tools to express the severity of their pain to healthcare professionals without resorting to overused metaphors that may not be believed, 40 reflecting the difficulty in accurately communicating the lived experience of pain.…”
Section: Types Of Painmentioning
confidence: 99%
“…3,26,27 These difficulties mean that patients may not be believed or find it difficult to communicate the severity of their pain without resorting to cliches. 40 Furthermore, if clinicians 39,40 focus on presentation of cyclical pain as a diagnostic factor, 46,52 women who present with other experiences, such as random or constant pain may be disbelieved adding to delays in diagnosis and treatment and feelings of frustration and disempowerment. 39 Issues of uncertainty around aspects of endometriosis such as cause, diagnosis and the best treatment can affect how women and health professionals interpret and manage the pain 26 and creating issues for diagnosing endometriosis through presentation of cyclical pain.…”
Section: Clinical Implications Of Findingsmentioning
confidence: 99%